Value for Money Government Budget Performance - Maulana, Ahmad; Alim, Rizky Zainul; Djasuli, Mohammad (International Journal of Education, Information Technology, and Others, 2024)
The purpose of writing this study is to know and analyze the improvement of Government budget performance based on Value for Money. This research uses the literature review method or also known as the literature review method. Researchers have conducted a source search through the Google Scholar site and determined that there are 10 articles in accordance with the criteria that researchers expect based on a total of 16,900 articles published in the 2015-2024 time frame. After conducting a literature study related to sources relevant to the research topic, it can be drawn to know that in general the performance of public sector budgets, including the government, is strongly influenced by the concept of money of value. A good government system is certainly needed to be implemented in the country. The government sector should be able to provide good quality services.